(untitled) (Journal of Renal and Hepatic Disorders, 2017)
Some authors affirm that early liver transplant (LT) provides excellent short-term survival in patients with severe alcoholic hepatitis (SAH) (1–4) and similar rates of alcohol relapse compared to patients with 6 months of abstinence. We agree with the choice of not excluding patients who manifest their decompensation with bleeding and infections (common complications of SAH) and patients with psychiatric comorbidities. Data from the literature have stated for a long time that the approach to patients with alcoholic liver disease (ALD) should be changed with no ethical or technical preconceptions. The reasons in favor of this change are as follows: